A Note on Ciris 218 - Olszaniec, Włodzimierz (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
This article contains a suggestion concerning the Ciris. The author tries to explain the reasons for the corruption in verse 218 and offers a tentative solution.